Hubungan Dukungan Keluarga dengan Kepatuhan Pola Diet Rendah Purin di Desa Sepang Kabupaten Buleleng - Ni Ketut Putri Marthasari; I Wayan Antariksawan Antariksawan; Anak Agung Ngurah Putu Putra Negara (Politeknik Negeri Jember, 2025)
Gouty arthritis is caused by hyperuricemia, which results in the accumulation of purine crystals in the joints, leading to pain and limitations in daily activities. This descriptive correlation study investigated the association between family support and adherence to a low-purine diet among 100 individuals with gout in Sepang Village, Busungbiu District, Buleleng Regency. Spearman's rank correlation test identified a statistically significant, albeit very weak, positive association between family support and dietary adherence, with a correlation coefficient of p= 0.041 (p<0.05). These findings indicate that family support may contribute to improved adherence to a low-purine diet among individuals with gouty arthritis. Keywords: gout arthritis, family support, dietary compliance